Perspektif dalam Pendidikan Matematika dan Implikasinya terhadap Proses Pembelajaran - Tasya Maria Agustin Marpaung; Syalsabilah Alamsyah; Adrianus R. Piran; Nasywa Mahesa (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
As a core academic discipline, mathematics contributes substantially to shaping learners' rational, critical, and orderly thinking. Even so, classroom practice still reveals a range of obstacles that leave students struggling to grasp concepts and work through mathematical problems. This paper sets out to review what mathematics learning is meant to achieve, the difficulties students commonly face, and how teachers can help address them. A literature-review approach was taken, drawing on a range of relevant scholarly sources. The review suggests that how well students learn mathematics hinges on their active involvement, how deeply they grasp the underlying concepts, and the instructional strategies teachers put to use. Such difficulties tend to stem from both internal and external factors that intertwine with one another. Teachers are therefore called upon to take on their roles fully as facilitators, mentors, motivators, and innovators so that learning becomes more meaningful. Adopting suitable instructional approaches is expected to lift both the learning process itself and students' mathematics achievement.